Volcanic succession, petrology, and geochemistry of the Sujiagou komatiite from the North China Craton. (19th July 2019) - Yang, Lihui; Tian, Wei; Hou, Guiting; Liu, Shuwen; Wang, Bin; Li, Jie; Chen, Mimi
Abstract : The ~2.7‐Ga Taishan greenstone belt from the Eastern Block of the North China Craton has well‐exposed komatiite sections. The komatiite outcrops at Sujiagou have well‐preserved primary volcanic texture although they have experienced amphibolite‐facies metamorphism. Two komatiite lava flows are identified in the Sujiagou outcrops: "Flow Ι, " with a thickness of 55 m, is characterized by poly‐sutured crust at the top, spinifex texture in the middle, and olivine cumulates at the flow bottom. "Flow ΙΙ" consists of abundant pahoehoe lava lobes with no interstitial materials. These volcanic characteristics, as well as the interbedding with terrestrial sediments, suggest that the Sujiagou komatiite erupted in a subaerial continental environment. The olivine–chromite geothermometer gives peak metamorphic temperatures from 684°C to 764°C. Phase equilibria modelling suggests that the mineral proportions and mineral compositions are consistent with a retrograde temperature of ~488°C, at which the komatiite would have low olivine Fo (79–89) and high bulk‐rock Mg # (83–90). Linear mixing of the in situ trace element compositions of the metamorphic olivine, augite, tremolite, serpentine, and chlorite from Sujiagou komatiite samples can reproduce the trace elements of representative komatiite compositions, suggesting that later metamorphism and fluid–rock interactions played key roles in trace element variations in the bulk‐rock komatiite samples. These results also imply that the "arc signature" of the Sujiagou komatiite may be an overprint from posteruption fluid alteration rather than a primary subduction geochemical feature. Therefore, the Sujiagou komatiites may belong to a part of the global plume‐related greenstone belts at ~2.7 Ga.